Ludopathy in the story «Amor de madre. Crónica de la época del virrey “Brazo de Plata”» by Ricardo Palma - Jurado Urbina, Danytza Mariella (2022)
This article seeks to describe the gambling addiction developed by the character don Fernando de Vergara in the story «Amor de madre. Crónica de la época del virrey “Brazo de Plata”», by Ricardo Palma. In order to reach and achieve this objective, we will take as a reference the analysis and data provided by the Diagnostic and Statistical Manual of Mental Disorders (DSM-V), which will be used to analyze gambling addiction in the aforementioned story. We know that literature refers to fictional spaces, but many times these are based on concrete references; hence, analyzing the behavior of a gambling addict in the space of literature will allow us to test an analysis of gambling addiction from the field of clinical psychology.